BEHAVIOR MANAGEMENT IN GEN Z FINANCES: INFLUENCE LITERACY FINANCE, COGNITIVE MATHEMATICS ECONOMY, AND SELF-CONFIDENCE - Widiastuti, C Tri; Tarigan, Liyandri Rasbina (Stability: Journal of Management and Business, 2024)
In the digital age, literacy financing is increasingly crucial in education. With excellent financial literacy, Generation Z can better grasp and respond to global finance trends. To understand the concepts stated, Gen Z must have the appropriate mathematical ability to make logical financial decisions, forecast the long-term consequences of economic decisions, and minimize financial losses due to errors. As a result, Generation Z must have self-sufficient trust to improve their ability to manage finances effectively and independently. Study This is a quantitative design research with primary data gathered by a questionnaire. Semarang City's population analysis focuses solely on Generation Z. The electoral sample was drawn using the convenience sampling methodology, rather than the probability sampling method. Data was analyzed using the Partial Least Squares (PLS) method and the soft SmartPLS version 3 device. The study's findings indicate that financial literacy, cognitive mathematics ability, and self-belief all favor and significantly impact financial behavior management. Trust in oneself also mediates the relationship between financial literacy, cognitive mathematical ability, and financial behavior management. Implication study This demonstrates that a strong understanding of linked literacy, financial, and cognitive mathematics, can boost Gen Z's self-trust in making productive and sensible financial decisions.